Emerging Hypersexuality in a Patient With Progressive Supranuclear Palsy - Pei Ling Lim; Boon Ceng Chai (BJPsych Open, 2025)
Aims: Progressive supranuclear palsy (PSP) typically presents with a constellation of motor symptoms, most commonly with frequent falls and gait disturbances. As the disease progresses, cognitive dysfunction and behavioural abnormalities may develop, however hypersexuality in the absence of the usage of dopaminergic agonists is rarely described. We report a case of a 70-year-old male referred to Consultation Liaison Psychiatry for inappropriate sexual behaviour on a background of Progressive Supranuclear Palsy with Predominant Cerebellar Ataxia.